Edmodo-based Blended Learning to Improving Mathematical Communication Skills and Self-regulated Learning of High School Students - Lidinillah, Upi; Cahya Mulyaning A, Endang; Dasari, Dadan (KnE Social Sciences, 2024)
This study aims to assess the improvement of mathematical communication skills and self-regulated learning in students who engage in Edmodo-based blended learning models. This research employed a quasi-experimental method. The study involved students from the first grade of high school, comprising 32 students from class MIPA 7 and 32 students from class MIPA 8. The instruments used included a test and a questionnaire. The data analysis utilized the t-test through SPSS 25.0 for Windows, specifically the Independent Sample T-test. The results indicated that 1) overall, Edmodo-based blended learning models is effective in improving students mathematical communication skills and self-regulated learning; 2) In the KAM category (high), Edmodo-based blended learning models are effective in improving students self-regulated learning; 3) The effectiveness of Edmodo-based blended learning models for students’ mathematical communication abilities is classified into medium categories. Edmodo-based blended learning has implications for teacher activeness by using technology in education and promotes student self-reliance in the learning process. Keywords: blended learning, emodo, mathematical communication skills, self-regulated learning